Urban Forests in Florida: Storm Damage Assessment Utility for Estimating Hurricane-Caused Tree Debris - Benjamin Thompson; Francisco Escobedo; Christina Staudhammer; Jerry Bond; Chris Luley (EDIS)
FOR268, a 5-page illustrated fact sheet by Benjamin Thompson, Francisco Escobedo, Christina Staudhammer, Jerry Bond, and Chris Luley, explains how the USDA Storm Damage Assessment Protocol (SDAP), or i-Tree Storm, can be used to better estimate tree debris amounts and cleanup costs for pre-hurricane planning purposes and post-hurricane response. Includes additionl literature. Published by the UF School of Forest Resources and Conservation, July 2010.